Un criterio que compara las estadísticas Q_i y DF beta_j(i) para el análisis de residuales en modelos de rango completo (2009)
This paper presents, a criterion to compare the Qi and DFβj(i) statistics, commonly used in the analysis of residuals to identify inﬂuential observations on the estimates of full rank linear models. The criterion uses the distribution of these statistics, under the classical assumption ei ∼ N(0;σ2) and Cov(ei,ej) = 0, i 6= j.